Minting, state, and economy in the Visigothic kingdom : from settlement in Aquitane through the first decade of the Muslim conquest of Spain - Kurt, Andrew (Amsterdam : Amsterdam University Press, 2020)
This study of the Visigothic kingdom monetary system in southern Gaul and Hispania from the fifth century through the Muslim invasion of Spain fills a major gap in the scholarship of late antiquity. Examining all aspects of the making of currency, it sets minting in relation to questions of state - monarchical power, administration and apparatus, motives for money production - and economy. In the context of the later Roman Empire and its successor states in the west, the minting and currency of the Visigoths reveal shared patterns as well as originality. The analysis brings both economic life and the needs of the state into sharper focus, with significant implications for the study of an essential element in daily life and government. This study combines an appreciation for the surprising level of sophistication in the Visigothic minting system with an accessible approach to a subject which can seem complex and abstruse.
Title from publisher's bibliographic system (viewed on 20 Nov 2020).
Keywords: Money -- Spain -- History -- To 1500.; Visigoths -- Spain; Spain -- History -- Gothic period, 414-711.